Pengaruh Inflasi, Suku Bunga Bank Indonesia, Debt to Equity Ratio, Ukuran Perusahaan dan Umur Perusahaan terhadap profitabilitas Perusahaan Sub Sektor Pertambanagan Batubara yang Terdaftar di BEI Tahun 2013-2017 - Fitri Amanda Zuchrinata; Irni Yunita (Universitas Putera Batam, 2019)
During 2013-2017, the mining sector’s profitability significantly decreased—most significantly on coal’s sub-sector. The decrease was determined by the company’s internal factors (Debt to Equity Ratio, the size and the age of the company) and external factors (inflation and Bank Indonesia’s interest rate). This research aims to test how such factors influence the company’s profitability, focusing on the coal companies’ sub-sectors listed in Bursa Efek Indonesia during 2013-2017. This research is classified as a causal-descriptive research which uses a quantitative method. The method used to analyze the data is panel regression as well as t-test and F-test to test the hypothesis. The result of this research shows that all the listed factors affect the profitability of the companies significantly. Partially, Debt to Equity Ratio affects negatively and significantly, whereas inflation, Bank Indonesia’s interest rate, the size and the age of the company do not significantly affect the company’s profitability